The Study on Hybridized Two-Band Superconductor. (18th April 2013) - Chanpoom, T.; Seechumsang, J.; Chantrapakajee, S.; Udomsamuthirun, P.
Abstract : The two-band hybridized superconductor which the pairing occurred by conduction electron band and other-electron band are considered within a mean-field approximation. The critical temperature, zero-temperature order parameter, gap-to-T c ratio, and isotope effect coefficient are derived. We find that the hybridization coefficient shows a little effect on the superconductor that conduction electron band has the same energy as other-electron band but shows more effect on the superconductor that conduction electron band coexists with lower-energy other-electron band. The critical temperature is decreased as the hybridization coefficient increases. The higher value of hybridization coefficient, lower value of gap-to-T c ratio, and higher value of isotope effect coefficient are found.